Public Perceptions of Income Tax Article 21 Exemption in Indonesia: A Netnographic Study of TikTok Discourse - Fitria Nur Risky Afifah; Muhammad Ridhwansyah Pasolo; Septyana Prasetianingrum; Iriana Auliyah; Fahrudin Pasolo (Eastasouth Institute, 2026)
Income Tax Article 21 is one of Indonesia’s most visible fiscal instruments because it is deducted directly from workers’ employment income. Although exemption or government-borne PPh 21 has been used as a stimulus to protect disposable income, its legitimacy depends on how society interprets its fairness, effectiveness, and administrative accessibility. This study examines public perceptions of PPh 21 exemption through a qualitative netnographic analysis of TikTok discourse. Data were collected from the comment section of one @metropolitan.id video discussing the policy, which generated 6.1 million views, 126,000 likes, and 8,553 comments. After screening, 8,310 comments were coded using thematic analysis within an interpretive netnographic framework. The findings reveal four major themes. First, the policy was evaluated through its direct effect on take-home pay, with salary and PPh-related comments dominating the discussion. Second, users connected the policy to structural burdens such as BPJS contributions and formal employment registration. Third, public debate centered on distributive justice, especially the perceived exclusion of informal and unstable workers. Fourth, support for the policy was conditional and often accompanied by aspirations for more concrete subsidies, such as electricity discounts. The study contributes to fiscal policy and public-sector accounting literature by showing that digital public discourse offers a naturalistic source of evidence for understanding policy legitimacy, trust, and citizen evaluation in the digital governance era.